Resection Arthrodesis of Sarcomas around the Knee: Five Year Survival Outcome from a Cancer Dedicated Institute (Journal of Pakistan Orthopaedic Association, 2024)
Objectives: The surgical removal of malignant bone tumors around the knee requires generous removal of soft tissue along with segments of the femur and tibia without having adequate tissue for reconstruction, however different reconstruction options are proposed after wide local excision of sarcoma around the knee joint the objective of our study is to evaluate the outcomes of reconstruction with knee arthrodesis.Methodology: Retrospective reviews of all of the patients who received tumor removal and knee arthrodesis in our facility from January 2005 to December 2015 were conducted. The primary outcome was measured by using musculoskeletal tumor society score (MSTS) and Lower Extremity Functional Score (LEFS). The secondary outcome was measured in terms of postoperative complications, Limb length discrepancy, and time to union, metastasis, and recurrence.Results: A total of 22 patients underwent resection arthrodesis of the knee sarcoma during the mentioned period, performed by using an ipsilateral fibula and contralateral anteromedial cortex of the tibia using dynamic compression plate in 20, and in two patient's Ilizarov apparatus was used. Bone union occurred in 17 (77.2%) patients while 12 (54%) patients had spontaneous union and in 05 (22.7%) patients bone grafting was required. 05 patients had nonunion and all of them had wound infections and ended up in amputation. The mean MSTS score was 67.8+/-4.3% while the mean Lower Extremity Functional Score (LEFS) is 61.2+/-3.7%. Male patients have a low MSTS score of 55.4+/-3.7% as compared to the female population with a score of 74.6+/-4.9%. (p